KOMPETENSIÂ PEDAGOGISÂ GURUÂ DALAMÂ PENGEMBANGANÂ SOSIALÂ EMOSIONALÂ ANAKÂ USIAÂ DINIÂ PADAÂ GUGUSÂ SEKOLAHÂ 11Â ARJOWINANGUNÂ KOTAÂ MALANG - rina rinawijayanti; muhammad akbar (Pedagogi : Jurnal Anak Usia Dini dan Pendidikan Anak Usia Dini, 2016)
ThisÂ  studyÂ  wasÂ  conductedÂ  toÂ  determineÂ  (1)Â  theÂ  businessÂ  conductedÂ  byÂ  theÂ  teacherÂ  to provideÂ  theÂ  infrastructureÂ  basisÂ  forÂ  developmentÂ  ofÂ  socialâ€emotionalÂ  earlyÂ  childhoodÂ  (2) theÂ  learningÂ  processÂ  forÂ  theÂ  developmentÂ  ofÂ  socialâ€emotionalÂ  alreadyÂ  implemented teacherÂ  atÂ  schoolÂ  (3)Â  theÂ  monitoringÂ  andÂ  evaluationÂ  ofÂ  developmentÂ  capabilitiesÂ  socialâ€emotionalÂ  earlyÂ  childhoodÂ  teachersÂ  inÂ  theÂ  schoolÂ  haveÂ  beenÂ  implemented.Â  ThisÂ  studyÂ  uses aÂ  qualitativeÂ  caseÂ  studyÂ  method,Â  andÂ  SpradleyÂ  modelsÂ  usingÂ  analyticalÂ  techniques.Â  Based onÂ theÂ researchÂ conducted, theÂ researchÂ aspectsÂ ofÂ theÂ provisionÂ ofÂ infrastructureÂ facilities basicÂ  socialÂ  developmentÂ  emotionalÂ  earlyÂ  childhoodÂ  are:Â  (1)Â  teachersÂ  doÂ  notÂ  haveÂ  a descriptionÂ ofÂ theÂ toolsÂ forÂ socialÂ developmentÂ emotionalÂ earlyÂ childhood,Â (2)Â development ofÂ socialÂ skillsÂ emotionalÂ earlyÂ childhoodÂ wasÂ centeredÂ onÂ theÂ teacher,Â (3)Â emotionalÂ social learningÂ  toolsÂ  thatÂ  haveÂ  notÂ  beenÂ  revitalized.Â  InÂ  theÂ  aspectÂ  ofÂ  theÂ  processÂ  andÂ  strategyÂ  forÂ theÂ  establishmentÂ  ofÂ  socialÂ  andÂ  emotionalÂ  learning,Â  isÂ  onlyÂ  focusedÂ  onÂ  imitationÂ  and habituationÂ  andÂ  thereÂ  hasÂ  beenÂ  noÂ  specificÂ  programÂ  ofÂ  habituationÂ  behaviorÂ  withÂ  the specificÂ  objectiveÂ  ofÂ  socialÂ  aspectsÂ  ofÂ  emotionalÂ  developmentÂ  ofÂ  youngÂ  children.Â  WhileÂ  the monitoringÂ  andÂ  evaluationÂ  aspects:Â  (1)Â  monitoringÂ  andÂ  evaluationÂ  effortsÂ  areÂ  notÂ  focused onÂ  theÂ  child,Â  butÂ  theÂ  endingÂ  orÂ  theÂ  resultÂ  ofÂ  imitationÂ  thatÂ  hasÂ  beenÂ  done,Â  (2)Â  monitoring andÂ  evaluationÂ  ofÂ  socialÂ  emotionalÂ  learningÂ  onlyÂ  atÂ  theÂ  endÂ  orÂ  summarizeÂ  theÂ  behaviorÂ  of pupils.Â  (3)Â  psikotesÂ  AUDÂ  neverÂ  becomeÂ  referenceÂ  materialÂ  preparation ofÂ  theÂ  learning program.Â  (4)Â  monitoringÂ  andÂ  evaluationÂ  ofÂ  socialÂ  emotionalÂ  learningÂ  onlyÂ  takeÂ  placeÂ  if thereÂ areÂ obstaclesÂ orÂ disputesÂ pupil.